Optimized protocol for shotgun label-free proteomic analysis of pancreatic islets - SanchesTrevizol, Juliana; Dionizio, Aline; Delgado, Aislan Quintiliano [UNESP]; Ventura, Talita Mendes Oliveira; Da Silva Ribeiro, Caroline Fernanda; Buzalaf, Nathalia Rabelo; Bosqueiro, José Roberto [UNESP]; Buzalaf, Marília Afonso Rabelo (Oxford University Press (OUP), 2024)
Pancreatic islets are crucial in diabetes research. Consequently, this protocol aims at optimizing both the protein-extraction process and the proteomic analysis via shotgun methods for pancreatic islets. Six protocols were tested, combining three types of chemical extraction with two mechanical extraction methods. Furthermore, two protocols incorporated a surfactant to enhance enzymatic cleavage. The steps involved extraction and concentration of protein, protein quantification, reduction, alkylation, digestion, purification and desalination, sample concentration to ∼1 μl, and proteomic analysis using the mass spectrometer. The most effective protocol involves either a milder chemical extraction paired with a more intensive mechanical process, or a more robust chemical extraction paired with a gentle mechanical process, tailored to the sample's characteristics. Additionally, it was observed that the use of a surfactant proved ineffective for these types of samples. Protocol 5 was recently used with success to examine metabolic changes in pancreatic islets of non-obese diabetic mice exposed to low doses of fluoride ions (F-) and the primary pathways altered by the treatment.
Keywords: NOD islets; proteomic; protocol; shotgun